2006
DOI: 10.1016/j.neuron.2006.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Gating of CaMKII Autonomous Activity by Drosophila CASK

Abstract: The ability of CaMKII to act as a molecular switch, becoming Ca(2+) independent after activation and autophosphorylation at T287, is critical for experience-dependent plasticity. Here, we show that the Drosophila homolog of CASK, also known as Camguk, can act as a gain controller on the transition to calcium-independence in vivo. Genetic loss of dCASK significantly increases synapse-specific, activity-dependent autophosphorylation of CaMKII T287. In wild-type adult animals, simple and complex sensory stimuli c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 54 publications
9
67
1
1
Order By: Relevance
“…The modulatory effects on presynaptic calcium handling reversed within 5 min of washing out the peptide, while the postsynaptically recorded effects persisted long afterward. CaMKII is autophosphorylated following Ca 2ϩ /calmodulin activation, resulting in an increased affinity for the calmodulin complex, prolonging the time that the kinase is active (Hodge et al, 2006). In addition, autonomic activity of the phosphorylated kinase complex, even after the calmodulin complex has dissociated from the complex, further prolongs the active state (Hudmon and Schulman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The modulatory effects on presynaptic calcium handling reversed within 5 min of washing out the peptide, while the postsynaptically recorded effects persisted long afterward. CaMKII is autophosphorylated following Ca 2ϩ /calmodulin activation, resulting in an increased affinity for the calmodulin complex, prolonging the time that the kinase is active (Hodge et al, 2006). In addition, autonomic activity of the phosphorylated kinase complex, even after the calmodulin complex has dissociated from the complex, further prolongs the active state (Hudmon and Schulman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Locomotor defects can be rescued by CASK-b expression in the nervous system: To confirm that these motor phenotypes stem from loss of CASK-b, we assayed the ability of a CASK-b cDNA transgene (used previously in Hodge et al 2006) to rescue locomotor performance using the UAS/Gal4 binary expression system (Fischer et al 1988;Brand and Perrimon 1993;Phelps and Brand 1998). We found that expression of CASK-b with a weak pan-neuronal driver (C155-Gal4 ) partially rescued all parameters that were previously deficient in CASK P18 flies (P , 0.05).…”
Section: P-element Excision Eliminates the Cask-b Isoformmentioning
confidence: 99%
“…The addition of CaMK-like and L27 domains to the MAGUK core would be expected to give CASK-b additional unique functionality compared with the shorter proteins. In particular, CASK-b has previously been shown to regulate the autophosphorylation of calcium/calmodulin-dependent protein kinase II (CaMKII) in a calcium-dependent manner via an interaction with the CaMK-like domain (Lu et al 2003;Hodge et al 2006).…”
mentioning
confidence: 99%
“…Moreover, analysis of CASK mutations in Drosophila melanogaster and C. elegans suggested several other functions. In Drosophila, CASK mutations produce a discrete neurological phenotype that includes aberrant regulation of activities mediated by calcium/calmodulin-dependent kinase II (15,16), and CASK may function by modulating Ca 2ϩ -calmodulin dependent protein kinase (17). In contrast, in C. elegans the CASK homolog Lin-2 is selectively required for vulval differentiation and proper localization of the EGF receptor LET-23 (5).…”
mentioning
confidence: 99%